Kerangka Evaluatif Integratif dalam Desain Interior Kafe: Menghubungkan Sustainable Interior Design dan Karakter Third Place - Miky Endro Santoso; Tessa Eka Darmayanti (Besaung : Jurnal Seni Desain dan Budaya, 2026)
Sustainable interior design studies tend to focus on the ecological performance of materials and systems, while studies on Third Place predominantly emphasize the quality of users’ social interactions within space. The separation of these two approaches indicates the limited availability of evaluative frameworks capable of examining ecological and social relations simultaneously in café interior design. This study aims to examine the integration of Sustainable Interior Design principles and Third Place characteristics in café interior design through an integrative evaluative framework. The research adopts a qualitative approach using a theory-driven evaluative case study strategy, with the interior design of Loka Rasa Café as a single case. The data consist of design documents, including conceptual narratives, spatial configurations, three-dimensional visualizations, as well as technical and material specifications, which are analyzed using an evaluative matrix based on sustainability and social space indicators. The findings reveal that ecological sustainability and Third Place characteristics do not operate as separate dimensions, but intersect in shaping the overall quality of interior space. Strategies such as the use of recycled materials, modular construction systems, and the optimization of natural ventilation and lighting not only enhance ecological performance but also reinforce spatial qualities that are inclusive, egalitarian, and conducive to social interaction. The novelty of this study lies in the development of an integrative evaluative framework that links ecological and social dimensions within a single indicator-based analytical model. The findings suggest that the quality of social interaction in informal public spaces can emerge as a direct consequence of sustainable design strategies. This study contributes to the development of a more holistic approach to interior design, although it is limited to a conceptual case and requires further validation through user-based empirical observation